MULTIVARIATE SPATIAL ANALYSIS OF ACTIVE FAMILY PLANNING USERS USING CHOROPLETH AND PIE CHART MAPPING IN KUPANG CITY - Sulla, Marbella Katarina; Syamruth, Yendris Krisno; Landi, Soleman (Universitas Airlangga, 2025)
Family Planning (FP) is defined as an effort to regulate births, encompassing the establishment of ideal birth spacing and age, as well as the management of pregnancies. This is achieved by advancing, protecting, and developing reproductive rights to foster a high-quality family unit. Information on active family planning in Kupang City is still presented in tabular form. This information cannot yet be used to view detailed information on active family planning users by geography. The research employed a descriptive epidemiological approach using an ecological study design. The research sample was all individuals who utilized family planning services, totaling 22,703 people. Statistical data from 2022 indicates that the target for active FP users was not met, reaching only 39.7%. Among these users, the majority, 21,831 (96%), are female. The contraceptive method most commonly chosen is injections, which account for 12,360 (54%) of users. Those aged over 30 years constitute the largest age group, numbering 11,555 (50.9%). Additionally, the family planning policy shows that 12,327 individuals (54%) have fewer than two children.